CORPUS-BASED ACTIVITIES USE REAL LANGUAGE DATA TO ENGAGE STUDENTS IN ACTIVE VOCABULARY LEARNING, ANALYSIS, AND APPLICATION (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2024)
This article explores the effectiveness of corpus-based training in enhancing the lexical competence of 5th-6th grade students. Corpus-based activities involve the use of authentic language data to engage students in active exploration, analysis, and application of vocabulary. The article discusses the benefits of corpus-based activities, including customization, language awareness, long-term retention, vocabulary use in context, collaborative learning, authentic assessment, transferable skills, research opportunities, and integration with language skills. It highlights the learner-centered approach and the development of lifelong vocabulary acquisition strategies. Additionally, the article emphasizes cultural insights, metalinguistic awareness, differentiated instruction, and the consolidation of vocabulary learning. The findings demonstrate the potential of corpus-based training to foster lexical competence and empower students as proficient language users.